Transparansi Keuangan UMKM melalui Otomatisasi Akuntansi Digital Berbasis Cloud - Ayu Miranti Kusumaningrum; Galuh Aninditiyah; N. A. Miftahul Huda (Universitas Sains dan Teknologi Komputer, 2025)
In the digital economy era, financial transparency has become a critical aspect for the sustainability and credibility of Micro, Small, and Medium Enterprises (MSMEs). Despite their substantial contribution to employment and economic growth, many MSMEs in Indonesia still rely on manual accounting systems, which limit the accuracy and traceability of financial reporting. This study aims to empirically examine the effect of cloud-based accounting automation on financial transparency among Indonesian MSMEs. Using a mixed-methods approach, the research collected quantitative data from 120 MSME respondents in Jakarta and West Java through structured questionnaires and qualitative data from six key informants through semi-structured interviews. The quantitative data were analyzed using simple linear regression, resulting in a coefficient of determination (R²) of 0.513 and a beta coefficient of 0.598 (p = 0.000), indicating a strong and significant influence of accounting automation on financial transparency. Qualitative findings also revealed improvements in real-time access, reporting accuracy, and transaction traceability. The study confirms that cloud-based digital accounting systems enhance financial transparency by enabling automated integration, audit trails, and timely reporting. These findings contribute to the literature on digital transformation in MSMEs and offer practical implications for policymakers, financial institutions, and software providers to accelerate technology adoption and improve financial governance in the MSME sector.